Behaviorism Philosophy of Education (Doctrine and Its Influence in the Context of Modern Education - Veranica, Nina (Journal of Innovation in Teaching and Instructional Media, 2024)
Behaviorism theory can be applied to children’s education. The basic concept of behaviorism is that the interaction between stimulus and response causes learning. This theory focuses on measurement because measurement is an important way to find out whether there is a change in behavior in children or not. By using this theory, teachers must determine learning objectives, carry out learning analysis, determine children’s initial characteristics and abilities, determine indicators of learning success, create teaching materials, create learning strategies, observe stimuli that may be given to children, such as exercises or assignments, observe and analyzing student responses, and providing effective reinforcement.